Association between depression and anemia in otherwise healthy adults. (30th May 2016) - Vulser, H.; Wiernik, E.; Hoertel, N.; Thomas, F.; Pannier, B.; Czernichow, S.; Hanon, O.; Simon, T.; Simon, J‐M; Danchin, N.; Limosin, F.; Lemogne, C.
Abstract : Objective: It remains debated whether anemia is associated with depression, independently of physical health factors. We report a large‐scale cross‐sectional study examining this association in adults free of chronic disease and medication from the general population. Method: Hemoglobin levels were measured among 44 173 healthy participants [63% men; mean [standard deviation] age = 38.4 (11.1) years] from the 'Investigations Préventives et Cliniques' (IPC) cohort study. Depression was measured with the Questionnaire of Depression 2nd version, Abridged. Logistic regression analyses were performed to examine the association between anemia and depression, while adjusting for a wide range of sociodemographic characteristics and health‐related factors (i.e., sex, age, living status, education level, occupational status, alcohol intake, smoking status, physical activity, and body mass index). Results: Depressed participants were significantly more likely to have anemia compared to non‐depressed participants, even after adjustment for sociodemographic and health‐related variables [odds ratio = 1.36; 95% confidence interval = (1.18; 1.57)]. Anemia prevalence increased with depression severity, suggesting a dose–response relationship ( P for trend <0.001). Conclusion: In healthy adults from the general population, we found a significant and robust association between depression and anemia. Further studies are needed to assess the longitudinal relationship between both conditions and determine the mechanisms underlying this association.